2016
DOI: 10.3109/10641963.2016.1163369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension among China’s Sichuan Tibetan population: A cross-sectional study

Abstract: Prevalence of hypertension in Sichuan Tibetan was significantly higher than the national level with low rates of awareness, treatment, and control of hypertension. Intervention measurements are needed to change some unhealthy lifestyles, behaviors, and habits in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…Also, the prevalence of hypertension in our study was much higher than the nationwide average 39 and than that found in some other regional studies, 40 41 but close to the recent study in the Sichuan Tibetan population. 42 The high prevalence of dyslipidaemia and hypertension might be ascribed to dietary preferences and other lifestyle issues of residents in Jilin Province. The cold weather limits people’s outdoor physical activity during the long winter, consequently increasing the risk of being overweight or obese and the related metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the prevalence of hypertension in our study was much higher than the nationwide average 39 and than that found in some other regional studies, 40 41 but close to the recent study in the Sichuan Tibetan population. 42 The high prevalence of dyslipidaemia and hypertension might be ascribed to dietary preferences and other lifestyle issues of residents in Jilin Province. The cold weather limits people’s outdoor physical activity during the long winter, consequently increasing the risk of being overweight or obese and the related metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Some have reported reverse gradient with education 23 while others have reported no relationship 24 25 Alcohol use was associated with higher prevalence of hypertension as seen in other studies. 26 Limited data from South Asia suggests higher blood pressure levels in alcohol users 27 and also higher probability of myocardial infarction in them than alcohol abstainers 28 unlike other population groups. Interestingly, the rise in prevalence of hypertension in survey 2 was significant even after adjusting for these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia was defined as a fasting serum uric acid higher than 420 μmol/L in men and 360 μmol/L in women, in line with Chinese guideline [ 6 ]. Hypertension was defined as a SBP of at least 140 mmHg, and/or a DBP of at least 90 mmHg, and/or use of antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
“…Ganzi Tibetan Autonomous Prefecture is a large high altitude area of Tibet, with distinct geographic characteristics and lifestyles compared with other areas of mainland China. People tend to eat a high-salt, fat-rich diet and drink alcohol, so the cardiovascular risk factors and level of cardiovascular disease are more serious [ 6 8 ]. Most studies in this area have investigated the prevalence of cardiovascular disease and risk factors including hypertension, diabetes mellitus, overweight or obesity, and dyslipidemia in Tibetan area [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%